2021
DOI: 10.3390/jcm10071517
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Preterm Delivery Based on the Previous Pregnancy?

Abstract: (1) Background: Preterm deliveries (PTD, <37 gestational weeks) which occur in 5–18% of deliveries across the world, are associated with immediate and long-term offspring morbidity, as well as high costs to health systems. Our aim was to identify risk factors during the first pregnancy ending at term for PTD in the subsequent pregnancy. (2) Methods: A retrospective population- based nested case−control study was conducted, including all women with two first singleton consecutive deliveries. Women with PTD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…More recently, researchers have turned their attention to the subsequent risk of preterm birth from complications when the first birth is term. [5][6][7] Finding similar results to ours, a study from Norway reported a two-fold increase in the risk of preterm birth when the previous births were term with at least one complication (pre-eclampsia, placental abruption, smallfor-gestational age, stillbirth or neonatal mortality), compared with an uncomplicated first term birth. 6 Consistent with our study, the authors also found little evidence for confounding by known demographic and lifestyle factors.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
See 4 more Smart Citations
“…More recently, researchers have turned their attention to the subsequent risk of preterm birth from complications when the first birth is term. [5][6][7] Finding similar results to ours, a study from Norway reported a two-fold increase in the risk of preterm birth when the previous births were term with at least one complication (pre-eclampsia, placental abruption, smallfor-gestational age, stillbirth or neonatal mortality), compared with an uncomplicated first term birth. 6 Consistent with our study, the authors also found little evidence for confounding by known demographic and lifestyle factors.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
“…One pathway that explains the association between complicated term birth and subsequent preterm birth is that the complications can also reoccur 8,9 . Recurrence has been well established for pre‐eclampsia, 10 placental abruption 11 and small‐for‐gestational age, 12 complications linked to ischaemic placental diseases, 13 with these complications acting as risk factors for preterm birth 5–7 . Another more complex explanation is that each complication is associated with an increased risk of other complications, 8,14 which is supportive of the hypothesis of shared underlying mechanisms 8 .…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations